2019
DOI: 10.1038/s41598-018-37090-9
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthetics upregulate nitric oxide generation in cord blood and adult human neutrophils

Abstract: Nitric oxide (NO) generation by systemic neonatal neutrophils is not clarified. It is also not known whether local anaesthetics (LAs) transferred to the fetal systemic circulation following maternal epidural blockade may affect this process. In the present study, NO generation was evaluated in neutrophils from cord blood (CB, n = 11) and adult blood (n = 10) following exposure to bupivacaine (0.0005, 0.005, 1 mM), lidocaine (0.002, 0.02, 4 mM) and ropivacaine (0.0007, 0.007, 1.4 mM) using flow cytometry, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…is provides a common model [48][49][50][51][52]; that particular NOsystem involvement is also behind lidocaine-induced adverse effects. e inconsistent points about NO-system involvement, different L-NAME and/or different L-arginine effects, in various events, may be related to the facts that the NO-lidocaine studies rarely applied the used complete application of NO-agents (i.e., both L-NAME and L-arginine, given both alone and together) with the investigated procedure or agent application [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…is provides a common model [48][49][50][51][52]; that particular NOsystem involvement is also behind lidocaine-induced adverse effects. e inconsistent points about NO-system involvement, different L-NAME and/or different L-arginine effects, in various events, may be related to the facts that the NO-lidocaine studies rarely applied the used complete application of NO-agents (i.e., both L-NAME and L-arginine, given both alone and together) with the investigated procedure or agent application [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…However, the data are scarce for neutrophils. Yet, few studies show that all three NOS isoforms are present and generate NO in adult human neutrophils (35). Moreover, MPO, a major factor in oxidizing products in neutrophils was shown to produce nitrating oxidants in vivo (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that lidocaine, in vitro and in humans (as well as in Kuli ńska's study of ropivacaine), enhanced NETosis in neutrophils at clinically relevant concentrations, thus having the possibility to change the course of inflammation and metastasis [118,119]. Kulinska et al also showed that LAs upregulate nitric oxide synthase (NOS) production by neutrophils, thus increasing NO synthesis [120]. Moreover, a recent meta-analysis showed that perioperative i.v.…”
Section: Local Anesthetics (Las)mentioning
confidence: 99%